Brucella abortus 2308ΔNodVΔNodW double-mutant is highly attenuated and confers protection against wild-type challenge in BALB/c mice. (May 2017) - Li, Zhiqiang; Wang, Shuli; Zhang, Jinliang; Yang, Guangli; Yuan, Baodong; Huang, Jie; Han, Jincheng; Xi, Li; Xiao, Yanren; Chen, Chuangfu; Zhang, Hui
Abstract: Brucellosis is an important zoonotic disease of worldwide distribution, which causes animal and human disease. However, the current Brucella abortus ( B. abortus ) vaccines (S19 and RB51) have several drawbacks, including residual virulence for animals and humans. Moreover, S19 cannot allow serological differentiation between infected and vaccinated animals. We constructed double deletion (ΔNodVΔNodW) mutant from virulent B. abortus 2308 (S2308) by deleting the genes encoding two-component regulatory system (TCS) in chromosome II in S2308.2308ΔNodVΔNodW was significantly reduced survival in murine macrophages (RAW 264.7) and BALB/c mice. Moreover, the inoculated mice showed no splenomegaly. The mutant induced high protective immunity in BALB/c mice against challenge with S2308, and elicited an anti- Brucella -specific immunoglobulin G (IgG) response and induced the secretion of gamma interferon (IFN-γ) and interleukin-4 (IL-4). Moreover, NODV and NODW antigens would allow the serological differentiation between infected and vaccinated animals. These results suggest that 2308ΔNodVΔNodW mutant is a potential live attenuated vaccine candidate and can be used effectively against bovine brucellosis. Highlights: The 2308ΔNodVΔNodW has low virulence in macrophages and mice. The 2308ΔNodVΔNodW can elicit an anti- Brucella -specific IgG response. 2308ΔNodVΔNodW imunizations induce a cellular response. 2308ΔNodVΔNodW induces protection against B. abortus challenge. 2308ΔNodVΔNodW could be a potential DIVA vaccine.